Communicating Risk for Obesity in Early Life: Engaging Parents Using Human-Centered Design Methodologies - Cheng, Erika R.; Moore, Courtney; Parks, Lisa; Taveras, Elsie M.; Wiehe, Sarah E.; Carroll, Aaron E. (Frontiers in Pediatrics, 2022)
Objective: Pediatricians are well positioned to discuss early life obesity risk, but optimal methods of communication should account for parent preferences. To help inform communication strategies focused on early life obesity prevention, we employed human-centered design methodologies to identify parental perceptions, concerns, beliefs, and communication preferences about early life obesity risk. Methods: We conducted a series of virtual human-centered design research sessions with 31 parents of infants <24 months old. Parents were recruited with a human intelligence task posted on Amazon’s Mechanical Turk, via social media postings on Facebook and Reddit, and from local community organizations. Human-centered design techniques included individual short-answer activities derived from personas and empathy maps as well as group discussion. Results: Parents welcomed a conversation about infant weight and obesity risk, but concerns about health were expressed in relation to the future. Tone, context, and collaboration emerged as important for obesity prevention discussions. Framing the conversation around healthy changes for the entire family to prevent adverse impacts of excess weight may be more effective than focusing on weight loss. Conclusions: Using human-centered design techniques, we identified views of obesity risk and parental preferences regarding communication of risk for young infants. This information can be leveraged to motivate parents to participate in obesity prevention efforts. Motivating families to engage in obesity prevention may require pediatricians and other health professionals to frame the conversation within the context of other developmental milestones, involve the entire family, and provide practical strategies for behavioral change.